Cardiac arrhythmias 3 months after hospitalization for COVID-19. (14th October 2021) - Ingul, C B; Grimsmo, J; Mecinaj, A; Trebinjac, D; Berger Nossen, M; Andrup, S; Stavem, K; Josefsen, T; Omland, T; Jensen, T
Abstract: Background: The long-term frequencies of cardiac arrhythmias in hospitalized coronavirus disease 2019 (COVID-19) patients have not been thoroughly investigated. Purpose: To describe the prevalence of cardiac arrhythmias, 3–4 months after hospitalization for COVID-19. Methods and results: Participants with COVID-19 discharged from five large Norwegian hospitals were invited to participate in a prospective cohort study. We examined 201 participants (44% females, mean age 58.5 years) with 24-hour electrocardiogram 3–4 months after discharge. Body mass index (BMI) was 28.3±4.5 kg/m 2 (mean ± SD), and obesity (BMI >30) was found in 70 participants (34%). Clinically significant arrhythmias were defined as; ventricular tachycardia (non-sustained or sustained), premature ventricular contractions (PVC) exceeding 200/24 h, or coupled PVC, atrial fibrillation/flutter, second-degree atrioventricular block (AV-block) type 2, complete AV-block, sinoatrial (SA) block exceeding 3 s, premature AV-nodal beats in bigeminy, supraventricular tachycardia (SVT) exceeding 30 s, and sinus bradycardia with less than 30 beats/min. High-sensitive cardiac troponin T (hs-cTnT) was measured at the 3-month follow-up. Results: Cardiac arrhythmias were found in 27% (n=54) of the participants. Ventricular premature contractions and non-sustained ventricular tachycardia were the most common arrhythmias, found in 22% (n=44) of the participants. Premature ventricular contractions were the most frequent cardiac arrhythmia. More than 200 PVCs per day were observed in 37 participants (18%) with a mean of 1300 PVC/day, and in 35 (95%) of these participants, the PVCs were polymorphic. Among 10 patients experiencing NSVT, 5 participants had previous CVD, including coronary heart disease (n=1), 1 atrial fibrillation, 2 venous thromboembolism, 4 heart failure. Atrial fibrillation was found in seven patients (3%), none of them of new-onset. SA block >3 seconds was only observed in one patient, and no incidence of high degree AV block was discovered. Pre-existing cardiovascular disease or hypertension (CVDH) were reported in 40% (n=81) of the participants. The CVDH group had an increased amount of arrhythmia compared to the group free of CVDH (p=0.04). High PVCs showed a fair correlation with hs-cTnT levels at 3 months (ρ=0.21 p=0.048). Conclusions: Three months following hospital discharge with COVID-19, cardiac arrhythmia was found in every fourth participant and was associated with a higher concentration of hs-cTnT at 3 months. The clinical implications of persistent ventricular arrhythmia following COVID-19 is not clear, but ventricular ectopy has been linked to increased risk of cardiac disease, including cardiomyopathy and sudden cardiac death. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): The National Association for Heart, Lung diseases and the Norwegian Health Association and Akershus University Hospital.